The Relationship between Slya DNA Binding Transcriptional Activator Gene and Escherichia Coli Fimbriae and Related with Biofilm Formation - AL, HASSAN M.; Ali, Mostafa M (جامعة المرقب - كلية التربية بالخمس, 2021)
In this study, we demonstrate that the conjugative pET28a plasmid influences biofilm formation by increasing the biomass of E. coli. The results showed that, when pET28a was inserted into E. coli, biofilm formation was significantly increased compared with the strains without plasmid. The findings revealed that the Congo red agar (CRA) aerobic culturing of 28°C and 37°C incubation was the same indicator of biofilm production. Nevertheless, other findings revealed that the E. coli MG1655, MG1655 ΔslyA were isolated from Congo red plates as a single colony and then regrooved again at 37°C and 28°C, MG1655 wild kind produced a red morphotype whereas MG1655 ΔslyA strain created a white morphotype. Collective finding recommended that the temperature has effect on biofilm formation owing to the expression of the E. coli slyA gene is temperature-regulated. Moreover, these finding indicate that MG1655 strains and strains have plasmids (pET28a) have ability to enhanced sedimentation level when comparing with ΔslyA strains. Finally, this study indicates that conversion of MG1655 with pET28a vector within the existence or nonexistence of slyA transcriptional activator gene did not influence cell aggregation.
Keywords: علم الأحياء -- أمراض الجهاز الهضمي -- الإشريكية القولونية -- الأحماض النووية